Towards an understanding of the relationship of functional literacy and numeracy to geographical health inequalities. (October 2015) - Moon, Graham; Aitken, Grant; Roderick, Paul; Fraser, Simon; Rowlands, Gill
Abstract: The relative contributions of functional literacy and functional numeracy to health disparities remain poorly understood in developed world contexts. We seek to unpack their distinctive contributions and to examine how these contributions are framed by place-based deprivation and rurality. We present a multilevel logistic analysis of the 2011 Skills for Life Survey (SfLS), a representative governmental survey of adults aged 16–65 in England. Outcome measures were self-assessed health status and the presence of self-reported long-term health conditions. Exposure variables were functional literacy (FL) and functional numeracy (FN). Age, sex, individual socio-economic status, ethnicity, whether English was a first language, non-UK birthplaces, housing tenure and geography were included as potential confounders and mediators. Geography was measured as area-based deprivation and urban/rural status. FL and FN were both independently associated with self-assessed health status, though the association attenuated after taking account of confounders and mediators. For long-term conditions, the association with FN remained significant following inclusion of confounders and mediators whilst FL attenuated to non-significance. Rurality did not influence these associations. Area deprivation was a significant factor in attenuating the association between FL and self-assessed health status. Policy makers and health professionals will need to be aware of the distinctive impact of FN as well as FL when combating health inequalities, promoting health and managing long-term conditions. Highlights: Tests association of literacy, numeracy and health in developed world setting. Multilevel controls for relevant individual and contextual factors. Functional literacy and numeracy both associated with self-assessed health. Functional numeracy but not literacy associated with long-term illness. Area deprivation attenuates associations with literacy.